2004 43rd IEEE Conference on Decision and Control (CDC) (IEEE Cat. No.04CH37601) 2004
DOI: 10.1109/cdc.2004.1430280
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to vision-based formation control

Abstract: This paper implements several methods for performing vision-based formation flight control of multiple aircraft in the presence of obstacles. No information is communicated between aircraft, and only passive 2-D vision information is available to maintain formation. The methods for formation control rely either on estimating the range from 2-D vision information by using Extended Kalman Filters or directly regulating the size of the image subtended by a leader aircraft on the image plane. When the image size i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 23 publications
0
40
0
1
Order By: Relevance
“…In [10] a leaderfollower control is proposed based on input-output feedback linearization. In [11] distance is achieved using an Extended Kalman Filter and a neural network. In [12] a leader-follower approach based on feedback linearization is proposed.…”
Section: A Related Workmentioning
confidence: 99%
“…In [10] a leaderfollower control is proposed based on input-output feedback linearization. In [11] distance is achieved using an Extended Kalman Filter and a neural network. In [12] a leader-follower approach based on feedback linearization is proposed.…”
Section: A Related Workmentioning
confidence: 99%
“…The main limitation of the approach is given by the necessary multiple assumptions made about the aircraft dynamics; therefore, the controller only performs as desired in a limited flight envelope. However, as shown in the technical literature, the flight envelope has been expanded greatly using adaptive control [14,[35][36][37], fuzzy logic [38], and neural network (NN) [34,39] approaches.…”
Section: Introductionmentioning
confidence: 99%
“…(Giulietti et al 2000) simulated the scenario with the presence of a failure of one of the nodes, such as the loss of an aircraft. Experimental studies for evaluating the aerodynamic effects of formation flight and for validating formation control laws have been conducted with both wind tunnel experiments (Gingras 1999) (Fowler & D'Andrea 2003) (Kutay et al 2005) and flight-testing (Napolitano 2005) (Gu et al 2006) (Lavretsky 2002) (How et al 2004) (Johnson et al 2004). Related to flight-testing efforts, the NASA Dryden Flight Research Center Autonomous Formation Flight (AFF) project in 2001 demonstrated formation control in the lateral and vertical channels with a pair of F/A-18 aircraft .…”
Section: Introductionmentioning
confidence: 99%
“…(How et al 2004) at MIT performed a 2-aircraft formation flight using timing control. (Johnson et al 2004) at Georgia Tech have been performing a series of vision-based formation flight since 2004. This chapter presents the research effort leading to the flight demonstration of autonomous formation flight using three YF-22 research aircraft designed, built, instrumented, and tested at West Virginia University (WVU).…”
Section: Introductionmentioning
confidence: 99%